Helical spin texture of surface states in topological superconductors - P M R Brydon; Andreas P Schnyder; Carsten Timm (New Journal of Physics, 2015)
Surface states of topological noncentrosymmetric superconductors (NCSs) exhibit intricate helical spin textures, i.e., the spin orientation of the surface quasiparticles is coupled to their momentum. Using quasiclassical theory, we study the spin polarization of the surface states as a function of the spin–orbit interaction and superconducting pairing symmetry. We focus on two- and three-dimensional fully gapped and nodal NCSs. For the case of nodal systems, we show that the spin polarization of the topological flat bands is controlled by the spin polarization of the bulk normal states at the bounding gap nodes. We demonstrate that the zero-bias conductance in a magnetic tunnel junction can be used as an experimental test of the surface-state spin polarization.